The role of magnetic resonance imaging in the diagnosis and screening of breast cancer in Brazil (Research, Society and Development, 2023)
This article seeks to elucidate, for the population and health professionals, the risks, benefits, disadvantages and main uses of magnetic resonance imaging in the screening and management of breast cancer in Brazil. In this way, articles and works in the area were searched, in Scielo bases, for the most current and relevant information in this scenario, within the last 5 years, explaining from the current reality of breast cancer in the country, to the principles of operation of this equipment, which represents a great evolution in imaging exams. As a result, a series of information was obtained that guarantees the indication of magnetic resonance imaging in breast cancer as a good tool to support clinical decisions and follow-up of patients. Thus, it was noted that even with the great technological support provided, good conduct and medical training are still essential for the application of knowledge correctly, guaranteeing the health and integrity of patients. Therefore, much is still expected from the evolution of the method and its improvement for the future, so that it can offer an even earlier and more reliable diagnosis, guaranteeing early treatment and improving the prognosis of affected patients.